Few-photon all-optical phase rotation in a quantum-well micropillar cavity - Kuriakose, T; Walker, PM; Dowling, T; Kyriienko, O; Shelykh, IA; St-Jean, P; Zambon, NC; Lemaître, A; Sagnes, I; Legratiet, L; Harouri, A; Ravets, S; et al. (Springer Nature, 2022)
Photonic platforms are an excellent setting for quantum technologies as weak photon–environment coupling ensures long coherence times. The second key ingredient for quantum photonics is interactions between photons, which can be provided by optical nonlinearities in the form of cross-phase modulation. This approach underpins many proposed applications in quantum optics1,2,3,4,5,6,7 and information processing8, but achieving its potential requires strong single-photon-level nonlinear phase shifts as well as scalable nonlinear elements. In this work we show that the required nonlinearity can be provided by exciton–polaritons in micropillars with embedded quantum wells. These combine the strong interactions of excitons9,10 with the scalability of micrometre-sized emitters11. We observe cross-phase modulation of up to 3 ± 1 mrad per polariton using laser beams attenuated to below the average intensity of a single photon. With our work serving as a stepping stone, we lay down a route for quantum information processing in polaritonic lattices.